FINANCIAL PERFORMANCE EVALUATION OF PT BANK MANDIRI (PERSERO) Tbk. 2021 – 2023 USING DUPONT METHOD ANALYSIS - Zuliyana Zuliyana; Rosalinda Ayu P.; Istiono Istiono (CV. Adiba Aisha Amira, 2025)
This study aims to evaluate the financial performance of PT Bank Mandiri (Persero) Tbk. during the period of 2021 to 2023 using the DuPont Analysis method. This method is applied to assess how effectively the company generates profit through operational efficiency, asset utilization, and capital structure. The analysis focuses on four key components: Net Profit Margin (NPM), Total Assets Turnover (TATO), Return on Investment (ROI), and Return on Equity (ROE). The results show a consistent increase in NPM, ROI, and ROE over the three-year period, indicating improved efficiency and profitability. However, the TATO value remained stable and relatively low, suggesting the need for better asset utilization. Overall, the evaluation indicates that PT Bank Mandiri is in a healthy financial position and has a promising outlook in maintaining its competitiveness within the banking industry.